모래놀이치료에서 악기의 상징적 의미 - 곽현정 (심리상담 및 모래놀이치료(구 학교상담 및 모래놀이), 2025)
본 연구는 모래놀이치료 과정 중 제작되는 모래놀이 작품에 등장한 악기의 상징성을 살펴보고자 하였다. 철학과 예술에서 인식되며 표현되었던 상징(Symbol)은 심리학적 개념으로 사용되면서 심리치료에서 광범위하게 연구되어 왔다. 상징의 의미와 치료적 영향은 모래놀이치료에서도 중요한 연구주제가 되어왔다. 악기는 성경 및 동서양의 신화와 민담 등에서 치유와 치료, 감정의 표현, 물과 공기처럼 흐르는 여성성의 특성 및 조화의 균형, 질서 등 다양한 상징성을 내포하고 있다. 본 연구는 모래놀이 작품에 등장한 악기가 어떻게 악기의 다양하고 다층적인 상징성을 표현하는지에 대해 사례를 통해 살펴보고자 하는데 그 목적이 있다. 연구 결과 모래놀이 작품에 등장하는 악기는 치유, 감정, 욕망, 죽음 혹은 퇴행, 여성성, 조화 등 다양한 상징적 의미를 내포하고 있었다. This study aimed to examine the symbolism of musical instruments appearing in sandplay works produced during sandplay therapy. Symbols began to be recognized and explored in philosophy and art, and have been widely studied in psychotherapy as they have been used as psychological concepts. The meaning and therapeutic influence of symbols have also been an important research topic in sandplay therapy. Musical instruments contain various symbolisms such as healing and treatment, expression of emotions, characteristics of femininity flowing like water and air, balance of harmony, and order in the Bible and Eastern and Western myths and folk tales. The purpose of this study is to examine how musical instruments appearing in sandplay works express their diverse and multilayered symbolism through cases. The results of the study showed that musical instruments appearing in sandplay works contained various symbolic meanings such as healing, emotions, desire, death or regression, femininity and harmony. KCI Citation Count: 0